In an era of highly effective treatment, hepatitis C screening of the United States general population should be considered. (24th August 2017) - Younossi, Zobair; Blissett, Deidre; Blissett, Rob; Henry, Linda; Younossi, Youssef; Beckerman, Rachel; Hunt, Sharon
Abstract: Background & Aims: Hepatitis C virus (HCV) treatment with all oral direct acting antiviral agents (DAA's) achieve sustained virologic response (SVR) rates of 98%. Re‐assessment of general US population screening for HCV is imperative. This study compared the cost‐effectiveness (CE) of three HCV screening strategies: screen all (SA), screen Birth Cohort (BCS), and screen high risks (HRS). Methods: Using a previous designed decision‐analytic Markov model, estimations of the natural history of HCV and CE evaluation of the three HCV screening strategies over a lifetime horizon in the US population was undertaken. Based on age and risk status, 16 cohorts were modelled. Health states included: Fibrosis stages 0 to 4, decompensated cirrhosis, hepatocellular carcinoma, LT, post‐LT, and death. The probability of liver disease progression was based on the presence or absence of virus. Treatment was with approved all‐oral DAAs; 86% were assumed to be seen annually by a primary care provider; SVR rates, transition probabilities, utilities, and costs were from the literature. One‐way sensitivity analyses tested the impact of key model drivers. Results: SA cost $272.0 billion [$135 279 per patient] and led to 12.19 QALYs per patient. BCS and HRS cost $274.5 billion ($136 568 per patient) and $284.5 billion ($141 502 per patient) with 11.65 and 11.25 QALYs per patient respectively. Compared to BCS, SA led to an additional 0.54 QALYs per patient and saved $2.59 billion; compared to HRS, SA led to 0.95 additional QALYs per patient and saved $12.5 billion. Conclusions: Screening the entire US population and treating active viraemia was projected as cost‐saving.